Green‐Chemistry‐Inspired Synthesis of Cyclobutane‐Based Hole‐Selective Materials for Highly Efficient Perovskite Solar Cells and Modules. Issue 5 (16th December 2021) - Daskeviciute‐Geguziene, Sarune; Zhang, Yi; Rakstys, Kasparas; Kreiza, Gediminas; Khan, Sher Bahadar; Kanda, Hiroyuki; Paek, Sanghyun; Daskeviciene, Maryte; Kamarauskas, Egidijus; Jankauskas, Vygintas; Asiri, Abdullah M.; Getautis, Vytautas; et al.
Abstract: Hybrid lead halide perovskite solar cells (PSCs) have emerged as potential competitors to silicon‐based solar cells with an unprecedented increase in power conversion efficiency (PCE), nearing the breakthrough point toward commercialization. However, for hole‐transporting materials, it is generally acknowledged that complex structures often create issues such as increased costs and hazardous substances in the synthetic schemes, when translated from the laboratory to manufacture on a large scale. Here, we present cyclobutane‐based hole‐selective materials synthesized using simple and green‐chemistry inspired protocols in order to reduce costs and adverse environmental impact. A series of novel semiconductors with molecularly engineered side arms were successfully applied in perovskite solar cells. V1366 ‐based PSCs feature impressive efficiency of 21 %, along with long‐term operational stability under atmospheric environment. Most importantly, we also fabricated perovskite solar modules exhibiting a record efficiency over 19 % with an active area of 30.24 cm 2 . Abstract : A molecularly engineered cyclobutane‐based hole‐transporting material synthesised using simple and green‐chemistry‐inspired protocols achieves an impressive efficiency of 21 % in perovskite solar cells and over 19 % in perovskite solar module with an active area of 30.24 cm 2 .